The Effect Of Work Environment, Work Training and Empowerment of Employees on Improving Employee Performance In Population Office In Batam City: Pengaruh Lingkungan Kerja, Pelatihan Kerja dan Pemberdayaan Pegawai Terhadap Peningkatan Kinerja Pegawai Pada Dinas Kependudukan Kota Batam - Sumardin Sumardin; Sabri Sabri; Mustaqim Mustaqim (International Journal of Management and Business (IJMB), 2021)
This research has always played an active role, regulating all organizational activities, while being motivated by the presence of the company's success planners, agents and determinants within the organization. This survey aims to determine the impact of work environment, training, and talent enhancement on employee job satisfaction. Use multiple regression as the analysis method. The method used for the analysis is multiple regression, and the results of this study are important regression coefficients or work environment variables that affect the performance of some resident employees in Batam, Riau Islands. Hypothesis testing shows that the working environment of variables, professional training, and employee qualifications also affect employee performance. The author, who was proposed regarding the status of staff, suggests that the management staff of the Population Services in Batam, Riau Islands, be the first to obtain some job description. Specific conditions of work, outline of work, tasks to be done to discipline young employees